Social factors that predict cognitive decline in older African American adults. (25th September 2020) - Pugh, Erika; De Vito, Alyssa; Divers, Ross; Robinson, Anthony; Weitzner, Daniel S.; Calamia, Matthew
Abstract: Objectives: Projections from the United States Census Bureau suggest that the African American population may be the fastest growing race over the next 30 years and that they may be at the highest risk for developing dementia later in life. Various social factors have been shown to be associated with cognitive function and health outcomes. The present study aims to evaluate the relationship between social engagement and cognitive decline in a cohort of older African American adults. Methods: We utilized multilevel modeling to examine the association between cognitive decline and social engagement in a sample of 617 older African American adults. Results: Social activity was associated with global cognition, perceptual speed, perceptual orientation, and episodic memory over time. Loneliness was associated with better semantic memory performance over time. Perceived discrimination was associated with better semantic memory performance over time. Larger social network was associated with worse perceptual speed scores over time. Conclusions: Although our findings on loneliness and perceived discrimination over time were inconsistent with prior research, our findings on social activity and social network size over time were consistent with past literature and are thought to be due to positive social interactions providing a catalyst for cognitively stimulating activities. These results suggest that interventions designed to preserve cognition in African American older adults should incorporate adequate social activity. Furthermore, to maximize effectiveness, interventions should not necessarily focus on just expanding one's social network.